The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1023/a:1006501526018
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Injectable contraceptives are a valid option in every family planning program. Contraceptives which are administered every 2 or 3 months, containing only progestogen agents (DepoProvera, Noristerat) have proven efficacious and do not show long-term safety problems. They differ from other contraceptives in their long lasting action and by not presenting the contraindications of the estrogens. Their most prominent side-effect is the irregularity of cyclic bleeding. Although bleeding irregularities are not life t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This allowed us to exclude women who may have been using contraceptive injections. Contraceptive injections can result in irregular menstruation and altered androgen levels [12, 14]. We are thus able to better understand the relationship between adiposity and androgens and accordingly establish normative androgen data quantitatively taking into consideration BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed us to exclude women who may have been using contraceptive injections. Contraceptive injections can result in irregular menstruation and altered androgen levels [12, 14]. We are thus able to better understand the relationship between adiposity and androgens and accordingly establish normative androgen data quantitatively taking into consideration BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Women who did not report their menstrual cycle data (n=10), or lacked anthropometric measurements (n=1) or fasting serum samples (n=49) were also excluded. Because using exogenous hormone injections for contraception can result in irregular menstruation and altered androgen levels [14], we excluded women who indicated ever using contraceptive injections (n=173). The final study sample size for this analysis was n=494.…”
Section: Methodsmentioning
confidence: 99%
“…Women who did not report their menstrual cycle data (n = 10) or who lacked anthropometric measurements (n = 1) or fasting serum samples (n = 49) were also excluded. Because using exogenous hormone injections for contraception can result in irregular menstruation and altered androgen levels (De Aguilar et al 1997), we also excluded women who indicated ever using contraceptive injections (n = 173). Women responding “within the last 12 months” rather than choosing more specific responses of time frame for their last menstrual cycle were excluded due to ambiguity of the response (n=24).…”
Section: Methodsmentioning
confidence: 99%
“…However, we did not have data on contraceptive injections, which previous studies have found are the most commonly used contraception by Samoan women (Brewis et al 1998). Contraceptive injections can both stop menstrual cycles and alter serum androgen levels, masking the true prevalence of menstrual irregularity and hyperandrogenemia (de Aguilar et al 1997). …”
Section: Introductionmentioning
confidence: 99%